Statistical extended‐range forecast of winter surface air temperature and extremely cold days over China. (21st April 2017) - Zhu, Zhiwei; Li, Tim
Abstract : An extremely cold day (ECD) in boreal winter over China is often accompanied by freezing rainfall or snow, leading to power outages, paralysed traffic and damaged ecosystems. Extended‐range (5–30 days lead) forecast of Chinese winter surface air temperature (SAT) and ECD has become a critical demand nationwide. In the present study, based on training data during 1960/1961–1999/2000, a statistical spatial–temporal projection model (STPM) is conducted to carry out an independent extended‐range forecast of winter SAT and ECD over China. For the independent forecast period (2000/2001–2012/2013), STPM is able to capture the empirical orthogonal function (EOF)‐filtered 10–80 days SAT anomaly at all 5–30 days lead times. Verification against the observed 10–80 days SAT anomaly shows that significant temporal correlation coefficient skill persists to 25–30 days lead times over most parts of China, except for northeastern China and the Tibetan Plateau where useful skill is up to a 15 days lead time. Significant pattern correlation coefficients between forecasted and the EOF‐filtered/observed 10–80 days SAT anomaly account for over 63%/59% of total forecasts for all 5–30 days lead times. The forecast local ECD is determined based on reconstructed SAT by adding the lower frequency (longer than 80 days) climatological SAT to the forecast 10–80 days SAT anomaly. Except for southeastern China and the Tibetan Plateau, STPM can hit above 30% of local ECDs over most parts of China at least 15 days in advance.